Security Issues in Mobile NFC Devices - Roland, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This work provides an assessment of the current state of near field communication (NFC) security, it reports on new attack scenarios, and offers concepts and solutions to overcome any unresolved issues. The work describes application-specific security aspects of NFC based on exemplary use-case scenarios and uses these to focus on the interaction with NFC tags and on card emulation. The current security architectures of NFC-enabled cellular phones are evaluated with regard to the identified security aspects.
Introduction -- Basics -- Exemplary Use-Cases -- Related Work -- Tagging -- Card Emulation -- Software-based Relay Attacks on Existing Applications -- Summary and Outlook.
Keywords: Engineering; Computer security; System safety; Electrical engineering; Engineering; Communications Engineering, Networks; Systems and Data Security; Information Systems Applications (incl. Internet).; Security Science and Technology; Electronic books